ON THE APPLICATION OF THE PROJECT METHOD TO THE STUDY OF MATHEMATICS BY STUDENTS OF TECHNICAL - Dyussembayeva, Г.; Nugumanov, Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The article is devoted to current issues of the quality of training specialists. The authors present an attempt to find an answer to a frequently asked question from students: whether programmers, engineers need to learn the fundamental sciences, in particular the basics of mathematical knowledge. There is a problem with the content and methods of teaching mathematical disciplines. The abstractness of mathematical concepts, the lack of direct connection of concepts with professional activities leads to a decrease in motivation for their study. The article presents the experience of the project method application in learning the basics of mathematical disciplines by students of technical specialties, in particular on information and communication technologies. To solve the problem practical hypotheses are put forward, stating that the project on practical applications of mathematics fundamentals will allow future programmers to understand the importance of fundamental disciplines for professional activities, helps to increase motivation for the study of mathematics fundamentals. The example of the project on the themes "Application of elements of higher mathematics in computer games", "About application of elements of applied linear algebra in programming", results of comparative analysis of progress, motivation of students in the experimental and control groups are given. The study included a comparative analysis and questionnaires.